Patient-relevant costs for organ preservation versus radical resection in locally advanced rectal cancer - Wurschi, Georg; Rühle, Alexander; Domschikowski, Justus; Trommer, Maike; Ferdinandus, Simone; Becker, Jan-Niklas; Böke, Simon; Sonnhoff, Mathias; Fink, Christoph Andreas; Käsmann, Lukas; Schneider, Melanie; Bockelmann, Elodie; et al. (Cancers, 2024)
Total neoadjuvant therapy (TNT) is an evolving treatment schedule for locally advanced rectal cancer (LARC), allowing for organ preservation in a relevant number of patients in the case of complete response. Patients who undergo this so-called “watch and wait” approach are likely to benefit regarding their quality of life (QoL), especially if definitive ostomy could be avoided. In this work, we performed the first cost-effectiveness analysis from the patient perspective to compare costs for TNT with radical resection after neoadjuvant chemoradiation (CRT) in the German health care system. Individual costs for patients insured with a statutory health insurance were calculated with a Markov microsimulation. A subgroup analysis from the prospective “FinTox” trial was used to calibrate the model’s parameters. We found that TNT was less expensive (−1540 EUR) and simultaneously resulted in a better QoL (+0.64 QALYs) during treatment and 5-year follow-up. The average cost for patients under TNT was 4711 EUR per year, which was equivalent to 3.2% of the net household income. CRT followed by resection resulted in higher overall costs for ostomy care, medication and greater loss of earnings. Overall, TNT appeared to be more efficacious and cost-effective from a patient’s point of view in the German health care system.
Gesehen am 08.10.2024